Dynamic flow behavior and performance of a reactor coolant pump with distorted inflow - Li, Yi-bin; Fan, Zhao-jing; Guo, Dong-sheng; Li, Xiao-bin (Engineering applications of computational fluid mechanics, 2020)
In the operation of a nuclear plant system, a distorted inflow of a reactor coolant pump appears owing to the steam generator channel head and multi-bend, leading to the deterioration of pump performance and stability. In the present study, three-dimensional numerical calculations of three model geometries are carried out using block grid technology, with RNG k-ε and DDES model applied in the steady and transient simulation. The simulation results are validated with an experiment testing the pump with a short inlet pipe. As for the results, under the distorted inflow condition, the pump head and efficiency are reduced by 4% and 5.2% respectively at the nominal flow rate. Additionally, when the pump is coupled with upstream structures, the inlet flow becomes distorted and more chaotic, and the swirl and radial flow are produced by asymmetric pressure difference. Meanwhile, a pair of local vortices appears in the inlet section, forming re-distributed mass flow rates. As the distorted flow enters the pump, the blade inlet pressure and flow rate are unevenly distributed. Moreover, the evolution process of the vortex is accompanied with strong non-uniformity in the impeller channel, and thus asymmetric tangential force is imposed on the blades, increasing the risk of the fatigue breakdown of the impeller.